2020
DOI: 10.1073/pnas.2010428117
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo atlas of host–pathogen transcriptomes during Streptococcus pneumoniae colonization and disease

Abstract: Streptococcus pneumoniae (Spn) colonizes the nasopharynx and can cause pneumonia. From the lungs it spreads to the bloodstream and causes organ damage. We characterized the in vivo Spn and mouse transcriptomes within the nasopharynx, lungs, blood, heart, and kidneys using three Spn strains. We identified Spn genes highly expressed at all anatomical sites and in an organ-specific manner; highly expressed genes were shown to have vital roles with knockout mutants. The in vivo bacterial transcriptome during colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 71 publications
(100 reference statements)
4
57
0
Order By: Relevance
“…The vital role of these proteins in pneumococcal biology is highlighted by the fact that most clinical isolates of Spn carry both proteins (5,29,30), and mutants deficient in PspA and PspC are markedly reduced in virulence in a variety of experimental models (31)(32)(33)(34). PspA and PspC are among the most common and highly in vivo-expressed CBPs (5,14,29,35,36), and immunization with these proteins as antigens has been demonstrated to confer protection against invasive pneumococcal disease, especially when used in combination (31,37,38). Nonetheless, and despite .30 years of study on PspA and PspC, prior to this report, the role of the NPB in pneumococcal biology was undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…The vital role of these proteins in pneumococcal biology is highlighted by the fact that most clinical isolates of Spn carry both proteins (5,29,30), and mutants deficient in PspA and PspC are markedly reduced in virulence in a variety of experimental models (31)(32)(33)(34). PspA and PspC are among the most common and highly in vivo-expressed CBPs (5,14,29,35,36), and immunization with these proteins as antigens has been demonstrated to confer protection against invasive pneumococcal disease, especially when used in combination (31,37,38). Nonetheless, and despite .30 years of study on PspA and PspC, prior to this report, the role of the NPB in pneumococcal biology was undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, pneumococcal carriage is believed to be a prerequisite of invasive disease [85,86], which occurs when immunity is compromised, as is observed in the elderly. The transition from benign colonizer to lethal pulmonary or systemic pathogen also involves changes in bacterial transcript profiles and morphology [83,[87][88][89]. This was highlighted in recent studies that showed that the set of genes expressed by pneumococci during colonization were distinct from those expressed during lung infection as well as during bacteremia, indicating that the bacteria adapt to their host in an infection site/organ-specific manner [83,87].…”
Section: Pneumococcal Disease and The Elderlymentioning
confidence: 99%
“…The transition from benign colonizer to lethal pulmonary or systemic pathogen also involves changes in bacterial transcript profiles and morphology [83,[87][88][89]. This was highlighted in recent studies that showed that the set of genes expressed by pneumococci during colonization were distinct from those expressed during lung infection as well as during bacteremia, indicating that the bacteria adapt to their host in an infection site/organ-specific manner [83,87]. Importantly, sets of conserved genes were upregulated across the several strains tested, suggesting they could be potential vaccine targets that induce strain-independent protection [87,89].…”
Section: Pneumococcal Disease and The Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the expression of nanA and nanB in vivo has been established, previous in vivo studies examining the contribution of Spn's neuraminidases have yielded mixed results, [9,29,35,[37][38][39]. The lack of a colonization defect for the ΔnanA,nanB::janus mutant was surprising considering its robust mucus adherence phenotype.…”
Section: Plos Pathogensmentioning
confidence: 99%